PENYUSUNAN DRAFT STANDARD OPERATING PROCEDURE PROSES PENGOLAHAN TAHU - STUDI KASUS DI SENTRA PRODUKSI TAHU GUNUNG SULAH BANDAR LAMPUNG - Muhammad Iqbal Meyza; Otik Nawansih; Fibra Nurainy (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
A standard operating procedure (SOP) is a procedure or a sequence of steps which is standardized and must be passed to complete a particular work process (U.S. EPA., 2007). Arranging SOP draft is based on a review of Good Manufacture Practice. SOP is made for a guide line in doing process in an industry. In this research, a drafting SOP of the tofu industry was done by observating and recording every detail of the process. The research was conducted through four steps. Firstly, field observation to observe the process, this includes sanitation, tools specification, and description about step of processing the tofu. The Second step was determining the critical point and optimating the condition. The next step was arranging the SOP draft. The last step was testing of the SOP draft. Then the data were compared and discussed descriptively. The result showed that the implementation of SOP draft in Tofu Production gave tofu with better characteristic in flavor, aroma, color, compactness, appearance and texture which were prefered than the products made without using reference of the SOP draft. Key words: good manufacturing process standard operating procedure (SOP), tofu